Interface electronic structure at the topological insulator–ferrimagnetic insulator junction. (2nd December 2016) - Kubota, Y; Murata, K; Miyawaki, J; Ozawa, K; Onbasli, M C; Shirasawa, T; Feng, B; Yamamoto, Sh; Liu, R-Y; Yamamoto, S; Mahatha, S K; Sheverdyaeva, P; et al.
Abstract: An interface electron state at the junction between a three-dimensional topological insulator film, Bi2 Se3, and a ferrimagnetic insulator film, Y3 Fe5 O12 (YIG), was investigated by measurements of angle-resolved photoelectron spectroscopy and x-ray absorption magnetic circular dichroism. The surface state of the Bi2 Se3 film was directly observed and localized 3 d spin states of the Fe 3+ in the YIG film were confirmed. The proximity effect is likely described in terms of the exchange interaction between the localized Fe 3 d electrons in the YIG film and delocalized electrons of the surface and bulk states in the Bi2 Se3 film.